Fabrication of open section composite beam structures - Tan, Ze Lin. (2012)
The use of composite materials in the aerospace industries is increasing at an exponential rate. In order to manufacture certain structures that would be difficult to mould, the use of joint simplifies the problem greatly. Adhesively bonded joints would be preferred in the aerospace industries due to its light weight as compared to mechanical fasteners. Since I beams are commonly used to support bending loads, this project aims to study the effects of an adhesively bonded joint in composite I beams under 3 point bending conditions. 4 ply laminates of woven carbon-epoxy prepregs are moulded using aluminium square tubes and beams, and cured in the autoclave. Adhesive layers and additional prepreg layers are co-cured using the oven to further join 2 separate I beams. This I beam with the adhesive joint is compared with a control I beam of identical dimensions. 8 ply beams were fabricated in identical fashion. All the beams underwent 3 point bending tests using free weights, hydraulic rig and the MTS 810 machine. Strains and mid-span deflection was recorded to determine the stiffness and stress-strain relations of the beams. Results showed that the ‘8ply patch’ was able to perform as well as the ‘8ply control’ though its shear modulus decreased by 45.8%. Results of 4ply I beams were inconclusive as they were too flexible and twisted easily during the tests. Failure occurred when the web buckled for the 8 ply I beams and the ‘4ply control’. Delamination can be seen in the top flange of the joint of ‘8ply patch’. The presence of an adhesive joint had also prevented brittle failure.